Experimental investigations: Reinforced Concrete Beams Bending Strength with Brine Wastewater in Short Age - Husein A. Alzgool; Ahmad M. Shawashreh; Lujain A. Albtoosh; Basil A. Abusamra (Salehan Institute of Higher Education, 2024)
The scarcity of waste in some regions has led to the contemplation of other approaches to providing potable water for human use. In the present research, it is proposed that a portion of the brine wastewater be recycled for potable water purposes through its incorporation into concrete and reinforced concrete compositions. The researchers performed an extensive empirical investigation to examine the impact of incorporating brine wastewater into the concrete mixture on the shear strength, bending stress, and compressive strength of the material. A total of seventy-two beams, each measuring 500 mm in length, 100 mm in width, and 100 mm in depth, were observed. A total of twelve beams were designated as control specimens, while an additional sixty beams were subjected to immersion in brine wastewater at varying concentrations of 2.5, 5, 7.5, 10, and 15%. The beams were reinforced using two longitudinal steel bars with a diameter of 8 millimeters in the tension zone and 6 millimeters in the compression zone. The stirrups included in the study were also measured to have a diameter of 4 mm. The samples were examined at intervals of seven, fourteen, twenty-one, and twenty-eight days. Based on the findings of this study and other relevant studies, it was determined that the use of 10% fresh water as a substitute for brine wastewater yielded the most optimal outcomes. The results obtained after a duration of 28 days indicate a notable increase in both the compressive and bending strengths of the concrete samples, with improvements of around 22% and 2.6% seen in comparison to the reference specimens. The impact of brine wastewater on the corrosion of reinforcing steel in reinforced concrete was investigated. The empirical findings indicated that the introduction of brine wastewater at a concentration of 10% to the concrete constituents did not provide any discernible repercussions over a period of 65 days. Doi: 10.28991/CEJ-2024-010-01-010 Full Text: PDF